(untitled) (Eurasian Journal of Ecology, 2019)
The aim of the study was to analyze the current state of the main types of ecosystems of the Akzhayyk biosphere reserve based on field geobotanical and soil work in the surveyed territory, a retrospective analysis of climatic changes in the region over the past 38 years, the long-term dynamics of the hydrological parameters of the Zhayik (Ural) river, level and nature fluctuations and consequences for biota of overtaking phenomena on the northern coast of the Caspian Sea, the study of multi-temporal satellite images using remote sensing methods and GIS-technology. As a result, the periodic nature of changes in regional climatic data and hydrological parameters of the Zhayik (Ural) River, as well as the Caspian Sea was revealed. It is shown that climate change trends are expressed in a decrease in the average annual rainfall and a pronounced increase in the average annual air temperature, which entails consequences of an absolutely negative character for the Akzhayik reserve, taking into account the conditions of the arid zone in which it is located. Against the background of long-term fluctuations, a trend of a decrease in the water content of the Zhaiyk (Ural) River is revealed and a decrease in the level of the Caspian Sea occurs, which leads to a decrease in intrazonal meso- and hydromorphic ecosystems and a decrease in biodiversity. The effectiveness of monitoring the status of biogeocenoses of the project area based on remote sensing methods and GIS technologies is shown. Key words: Akzhaiyk biosphere reserve, hydrology, climate, Earth remote sensing methods, mapping, GIS technologies, Ural (Zhayik) river, anthropogenic transformation, ecosystem degradation.